Industrial networks and intelligent systems : second International Conference, INISCOM 2016, Leicester, UK, October 31-November 1, 2016, Revised selected papers /: second International Conference, INISCOM 2016, Leicester, UK, October 31-November 1, 2016, Revised selected papers. (2017) - Unknown
No abstract available